Water limitation reveals local adaptation and plasticity in the drought tolerance strategies of Bouteloua gracilis. Issue 1 (24th January 2023) - Bushey, Julie A.; Hoffman, Ava M.; Gleason, Sean M.; Smith, Melinda D.; Ocheltree, Troy W.
Abstract: As the frequency and severity of drought increase in many regions around the globe, quantification of key drought tolerance traits and the intraspecific variability of these traits will improve predictions of the vulnerability of a species to novel drought conditions. The objective of this study was to quantify the variability in drought tolerance traits and correlate this to the sensitivity of plant growth to different soil moisture levels across populations of Bouteloua gracilis . Fourteen populations of B. gracilis were sampled along one local elevation‐aridity gradient in northern Colorado and one latitude‐aridity gradient from South Dakota to New Mexico. Individuals from each population were clonally propagated and subjected to high and low soil moisture treatments in a greenhouse and were measured for gas exchange, midday water potential (Ψmid ), osmotic potential (Ψosm ), biomass production, and morphological traits. Under water‐abundant conditions, plants from the most arid region produced more total biomass (67%) than plants from the most mesic system, yet experienced the greatest sensitivity (−34%) when subjected to water limitation. Productivity was strongly and negatively correlated with the magnitude of osmotic investment across all populations: each megapascal of osmotic potential was correlated with a decrease of 2.3 g of biomass under water‐limited conditions. Gas‐exchange and leaf morphological measurements did not explain these patterns. Unlike plants from the mesic regions, plants from the most arid regions did not adjust Ψosm . This lack of plasticity may be a local adaptation and the likely source of increased sensitivity in these populations.